TECHNOLOGICAL ACTIONS FOR PROMOTING A DURABLE AGRICULTURE - BRAN, Mariana; ŞTEFAN, Marcela (Economics of Agriculture, 2008)
Sustainable agriculture means viable economical technologies, on a long period. Within this context, it attends to maintain and improve the physic environment, the resistance at external pressures, to gratify the population demand for food, to ensure for agricultural producers economic and social welfare. In the crop production, combining rationally and scientific the species, we can contribute to the improvement of those deteriorate areas by various factors. The real agriculture development involves a cautious administration of resources and environment.